Section 4: Clinical Pharmacy Services 2022
DOI: 10.1136/ejhpharm-2022-eahp.109
|View full text |Cite
|
Sign up to set email alerts
|

4CPS-072 Bezlotoxumab for the prevention ofClostridioides difficilerecurrence: study in the real world

Abstract: Patients' median age at NSCLC diagnosis was 62 (53-67) years; 73.3% (121/165) men; 69.09% (114/165) stage IIIB-V; 59.39% (98/165) adenocarcinoma; 58.18% (96/165) family history of cancer; 24.24% (40/165) previous lung disease; EGFR status: 10.91% (18/165) mutated. Chemotherapy agents: 18.29% (30/164) gemcitabine; 21.34% (35/164) paclitaxel; 24.39% (40/164); 35.98% (59/164). Nephrotoxicity: 17.58% (29/165).Patients carrying the CYP27B1-rs4646536 (p=0.0312; OR 0.32; CI 95% 0.10 to 0.84; AG vs AA); CYP27B1-rs3782… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1). Relevant articles were not included based on the inclusion of a recently published more representative cohort from the same sample 22–29 . Two studies were randomized trials (MODIFY I and II) 6 and the remaining were observational 11–16,30–34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Relevant articles were not included based on the inclusion of a recently published more representative cohort from the same sample 22–29 . Two studies were randomized trials (MODIFY I and II) 6 and the remaining were observational 11–16,30–34 .…”
Section: Resultsmentioning
confidence: 99%
“…Relevant articles were not included based on the inclusion of a recently published more representative cohort from the same sample. [22][23][24][25][26][27][28][29] Two studies were randomized trials (MODIFY I and II) 6 and the remaining were observational. [11][12][13][14][15][16][30][31][32][33][34] Overall, 1472 patients received BEZ (691 excluding RCTs).…”
Section: Included Studies and Baseline Characteristicsmentioning
confidence: 99%
“…(15) If they performed quantitative synthesis did the review authors carry out an adequate investigation of publication bias (small study bias) and discuss its likely impact on the results of the review? (16)…”
Section: Qualitymentioning
confidence: 99%
“…Within 12 weeks of receiving bezlotoxumab, there were nine (18.4%) recurrences. As nine patients died during the study, they were not included in the study and recurrence ratio is reported as 20.9% [16].…”
Section: Role Of Bezlotoxumab In the Prevention Of Recurrent C Difficilementioning
confidence: 99%